Search engine indexing storage optimisation using Hamming distance. (1st January 2012) - Kundu, Anirban; Sett, Siddhartha; Kumar, Subhajit; Sengupta, Shruti; Chaudhury, Srayan
We are going to propose indexing algorithm of search engine aiming to decrease time and space complexity. Existing indexing algorithms have greater space requirements due to the fact that all the words of the web pages are being stored except the stop words. In this paper, we present a theory on indexing mechanism of a search engine. Time complexity is the time taken by the search engine to retrieve information and space complexity is the space required to store the indices in the hard disk. Decreasing the time complexity will lead to faster retrieval of information and decreasing the space complexity leads to efficient utilisation of space. We have only dealt with textual part of the web pages. Hamming distance concept frames approach to achieve better result in space complexity.